Magic cube in mathematical learning by using augmented reality approach / Rabiatul Adawiah Ayop ... [et al.] - Ayop, Rabiatul Adawiah; Md Jahaya, Wan Zanariah; Yazid, Zainah; Shafi, Mohd Syukri; Sakawi, Muhammad Shazwan (2020)
This innovation was created to use the Augmented Reality (AR) approach in mathematical learning. Objective of the innovation is to create teaching aids that generate better understanding of students in mathematics subject, enhancing students' concentration in the class and improving students' exploration in learning mathematics. Magic Cube by using augmented reality was innovated as the teaching aids to achieve the objective. The overall process of innovation involved five intensive stages, i) identifying topic in mathematics concept to focus, ii) creating mathematics problem solving in the selected topic, iii) designing the problem solving in augmented reality, iv) coding the augmented reality with Quick Response (QR) Codes, and v) creating the Magic Cube and implementing codes on the Magic Cube. Magic Cube was tested to 18 students of Negeri Sembilan Matriculation College. The findings of students' feedback on the use of Magic Cube in mathematics learning showed a total of 66.7% of students strongly agreed that they understood all the examples used by lecturers when using Magic Cube. Bulk of the students (61.1%) felt comfortable when the lecturer used the Magic Cube. While 50% of students strongly agree that they concentrate, understand what is taught and confident when answering questions when Magic Cube is used in mathematics learning. The implementation of this innovation gives a very positive response to teaching and learning in the classroom assisted by augmented reality (AR) approach.